Yields, and nitrogen and phosphorus use efficiency as influenced by fertilizer NP additions in wheat (Triticum aestivum) under rice (Oryza sativa)-wheat and pigeonpea (Cajanus cajan)-wheat system on a Typic Ustochrept soil - SINGH, V K; DWIVED, B S; SHUKLA, ARVIND K (The Indian Journal of Agricultural Sciences, 2011)
AfIeld experinlent \vas conducted on a Typic Ustochrept soil ofModipuram during 1998-99 to 2000-01, to evaluatethe ctTcct offertilizer N and P rates on wheat (Triticum aestivuln L emend. Fiori & Paol.) yield, Nand P use efficiency, soilfertility, and apparent nutrient balances under rice  (Oryza sativa L.)-wheat and pigeonpea [Cajanus cajan (L.) MiIlsp.]\wheat systenls. Pigeonpea substitution for rice during monsoon season ,improved wheat yield by 16%, and total Nand Puptake in wheat  by 31 and I0~1J respectively. At these uptake, output: input ratio under pigeonpea-wheat system (i e 1.17for Nand 0.65  for P) were also greater con1pared with rice-wheat system. Averaged across fertilizer NP rates and years ofcxperitnentation the values ofagronolllic efficiencies ofN and P were greater by 3.7 kg/kg Nand 10.5 kg/kg P respectivelyin wl"eat following pigeonpea than that following rice. At the tennination ofthe experin1ent soil organic carbon and total Nin 0-15 C111 profile depth were increased (8 and 31% respectively) over the initial contents in the plots cropped withpigcOrtpca-wheat. The available Pcontent was, however, greater (80/0) under rice-wheat system. Continuous rice-wheatcropping led to increase jn soil bulk density (0.06 Mg/m 3), and a decline in total porosity (4.6%) over the initial values,particularly at J0-45 cm profile depth. Rice substitution forpigeonpea helped to maintaining these soil physical parametersat the initial level, and thus prevented sub-surface soil compaction. After 3-crop cycles apparent Nand P balance werepositive in both the systems and for all the treatments, except a negative N balance (84 kg/ha) under pigeonpea-wheatsysten1.